Use of a bDMARD or tsDMARD for the management of inflammatory arthritis under checkpoint inhibitors: an observational study. Issue 2 (21st October 2022) - De La Fuente, Fanny; Belkhir, Rakiba; Henry, Julien; Nguyen, Chi Duc; Pham, Thao; Germain, Vincent; Gavand, Pierre Edouard; Labadie, Céline; Briere, Claire; Lauret, Ambre; Cardon, Thierry; Mouterde, Gael; et al.
Abstract : Objective: There is limited experience regarding the use of biological disease-modifying antirheumatic drug (bDMARD) and JAK inhibitor (JAKi) for the management of immune checkpoint inhibitors (ICI)-induced inflammatory arthritis. We aimed to assess their efficacy and safety in this setting. Methods: Using the Club Rhumatismes and Inflammation French network, we conducted a multicentre, retrospective, observational study of patients with cancer diagnosed with inflammatory arthritis under ICI(s) and treated with bDMARD or JAKi. Clinical data were collected using a standardised case report form. Results: Twenty patients (60% men, median age 69.5 years) were included, with rheumatoid arthritis (RA)-like (n=16), polymyalgia rheumatica-like (n=2) or psoriatic arthritis-like (n=2) clinical presentation. Two patients had pre-existing RA. 90% were treated with glucocorticoids as first-line therapy and 60% received methotrexate prior to bDMARD or JAKi. Anti-interleukin-6 receptor (IL-6R) therapy was used in 13/20 patients (65%), leading to clinical improvement in 11/13 patients (85%), but one patient experienced intestinal perforation and cancer progression was noticed in 6/13 patients (46%). Tumour necrosis factor inhibitors were used in 5/20 patients (25%), with improvement in 4/5 patients (80%) and cancer progression was observed in 3/5 patients (60%). Two infections (diverticulitis and pneumonitis) were reported. Anakinra, baricitinib and ustekinumab were each used in one patient. Median duration of the bDMARD or JAKi was 17 weeks. Conclusion: Anti-IL-6R therapy is currently the most common strategy in patients with ICI-induced inflammatory arthritis and insufficient response to glucocorticoids and methotrexate, leading to improvement in >80%. Overall, cancer progression occurred in about half of patients and whether the bDMARD/JAKi impacted the tumour response remains to be determined.